2012
DOI: 10.1007/s12149-012-0624-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging characterization of benign and malignant pheochromocytoma or paraganglioma: comparison between MIBG uptake and MR signal intensity ratio

Abstract: In patients with pheochromocytoma or paraganglioma, iodine-131 MIBG uptake is able to differentiate between benign and malignant disease, while MR imaging is not useful for this purpose. The higher MIBG uptake observed in malignant lesions could reflect major tumor storage of catecholamines compared to benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In particular, storage catecholamine granules have been demonstrated within adrenal medullary tissue and Pheo tumour lesions [47]. Since MIBG uptake reflects the concentration of neurosecretory storage granules in chromaffin normal tissue and in the corresponding tumours, the higher MIBG uptake of lesions in patients with malignancies compared to those of patients with benign tumours, as we observed in our experience [49], suggests a higher concentration of catecholamine in malignant Pheo; thus, this difference could reflect different functional conditions with malignant lesions being more prone to catecholamine secretion crises compared to benign tumours. This observation might explain the severe hypertensive attacks that frequently occur in patients with malignant Pheo and might also justify the use of radiolabeled MIBG for therapeutic purposes in such patients when conventional treatments are not effective [52,53].…”
Section: Groupsupporting
confidence: 73%
See 2 more Smart Citations
“…In particular, storage catecholamine granules have been demonstrated within adrenal medullary tissue and Pheo tumour lesions [47]. Since MIBG uptake reflects the concentration of neurosecretory storage granules in chromaffin normal tissue and in the corresponding tumours, the higher MIBG uptake of lesions in patients with malignancies compared to those of patients with benign tumours, as we observed in our experience [49], suggests a higher concentration of catecholamine in malignant Pheo; thus, this difference could reflect different functional conditions with malignant lesions being more prone to catecholamine secretion crises compared to benign tumours. This observation might explain the severe hypertensive attacks that frequently occur in patients with malignant Pheo and might also justify the use of radiolabeled MIBG for therapeutic purposes in such patients when conventional treatments are not effective [52,53].…”
Section: Groupsupporting
confidence: 73%
“…Lesions that concentrate MIBG can be benign or malignant and the ability of MIBG scan for tumour detection depends on both tumour size and differentiation [7,48]. Our results demonstrated that quantitative analysis of MIBG uptake may differentiate between benign and malignant Pheo, while MR imaging using signal intensity ratio measurement is not useful for this purpose; in fact, MIBG uptake, measured as tumour lesion OD IR, was significantly higher in malignant lesions compared to benign disease; this finding could depend on larger tumour size of malignant Pheo, but no significant difference in this parameter, measured on MR images, was found [49].…”
Section: Groupmentioning
confidence: 58%
See 1 more Smart Citation
“…They demonstrated that the scoring system was highly specific and sensitive (91.5% and 100%, respectively) for detecting PPGL and is useful to discriminate normal adrenal 123 I-MIBG uptake from pheochromocytoma. Others have adopted this approach (19,23,33). However, a major disadvantage is that visual interpretation remains subjective and is highly observer-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, specificities of 123 I-MIBG scintigraphy range between 70% and 100% for pheochromocytomas and 84% and 100% for paragangliomas, whereas sensitivities range between 85% and 88% and 56% and 76%, respectively (14)(15)(16)(17). Physiologic uptake of 123 I-MIBG by normal adrenal glands can give false-positive results or obscure small lesions (18)(19)(20). The sensitivity appears to be lower for extraadrenal, metastatic, recurrent, and certain hereditary PPGLs (14,16,(21)(22)(23)(24).…”
mentioning
confidence: 99%